Ethnomatematics-Based Learning Media for Junior High School Mathematics using Rejang Lebong as Bengkulu Traditional House - Gusvarini, Elsa Putri; Zamzaili, Zamzaili; Haji, Saleh (Jurnal Pendidikan MIPA, 2022)
The purpose of this research is to develop the mathematics learning media with ethnomathematics base for SMP (Junior High School) students at traditional house of Rejang Lebong and the media must valid, practice and effective. The research which used is research which developed by using ADDIE model with 5 steps, they are: (1) Analysis, (2) Design, (3) Development, (4) Implementation, and (5) evaluation. The subjects in this research are 24 students of class VIII of SMP Negeri 36 Rejang Lebong. The data instrument which collected in this research consist of validity sheet, practical sheet and a sheet of concept understanding capability test. Data are analyzed by using descriptive statistics to describe the average from students’ concept understanding. Validity is analyzed by using Aiken Index. The result shows that mathematics learning media with ethnomathematics base at Rumah Adat Rejang Lebong is Valid with average Aiken Index score on material aspect is 0,81 and media aspect is 0,92 with valid criteria. Learning media has practical criteria from the teacher and students’’ point of view. Interactive learning media product with ethnomathematics has followed the effective criteria according to students’ capability in understanding the concept. It is showed from the percentage of students’ completeness achievement is 82,68% with average score is 83,33.Keywords: development research, ethnomathematics, rumah adat, concept understandingDOI: http://dx.doi.org/10.23960/jpmipa/v23i4.pp1382-1394